FACTORS OF FINANCIAL LITERACY, PERSONAL BEHAVIOR, AND FAMILY ON INVESTMENT AWARENESS OF GENERATION Z WORKERS - Dinar, Amanda (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2024)
This study aims to investigate the role of financial literacy, personal and family behaviors (such as saving behavior, self-control, spending patterns, and risk attitude) on investment awareness among Generation Z workers. Data were collected using purposive sampling through an online survey of Gen-Z workers who have worked or are currently working for at least 1 year and are aged 18-27 years in the Jabodetabek area. A total of 262 respondents were collected and then analyzed using PLS-SEM. Results show that financial literacy, self-control, saving behaviorrisk attitude, and family financial socialization have a significant influence on the investment awareness of Gen-Z workers. Meanwhile, self-control and spending patterns do not have a significant influence on the investment awareness of Gen-Z workers.